Life Prediction Methodologies and Data for Ceramic Materials 1994
DOI: 10.1520/stp12775s
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Existing and Newly Proposed Models for Creep Deformation and Life Prediction of Si3N4

Abstract: This paper summarizes recent experimental results, obtained at Oak Ridge National Laboratory (ORNL), on creep behavior and creep rupture of a commercial grade of Si3N4 ceramic in the temperature range of 1150°C to 1300°C. A uniaxial model capable of describing the behavior under general thermomechanical loading is introduced and compared with existing models. An exploratory extension of the new model to a multiaxial form is then discussed. Issues are also discussed concerning the standardization of data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Among those who studied this methodology was Jow-Lian Ding [53] who found that the results of the regression analyses indicated that the Minimum Commitment model fit the data slightly better than the Larson-Miller model. The reason was that this model has five independent variables whereas the Larson-Miller model has only two.…”
Section: Review Of the Minimum Commitment (Mc) Methodologymentioning
confidence: 99%
“…Among those who studied this methodology was Jow-Lian Ding [53] who found that the results of the regression analyses indicated that the Minimum Commitment model fit the data slightly better than the Larson-Miller model. The reason was that this model has five independent variables whereas the Larson-Miller model has only two.…”
Section: Review Of the Minimum Commitment (Mc) Methodologymentioning
confidence: 99%
“…Among those who have studied this methodology was Jow-Lian Ding et al . [ 27 ] who found that the results of regression analyses indicated that the Minimum Commitment model fitted the creep data studied only slightly better than the Larson-Miller model regardless of the high number of constants.…”
Section: Approaches To Creep Life Predictionsmentioning
confidence: 99%
“…A noted exception is the recent work by Ding et al (1994), as well as the work by White and Hazime (1995). Another exception is an article by Liu et al (1995) which is an extension of the work presented by Ding and coworkers.…”
Section: Introductionmentioning
confidence: 97%